Acute Kidney Injury in Children Undergoing Surgery for Congenital Heart Disease - Pedersen, Kirsten (European Journal of Pediatric Surgery, 2012)
Acute kidney injury (AKI) is a serious postoperative complication in children undergoing surgery for congenital heart disease. The incidence of this complication and its consequences may have changed due to advances in surgical technique, but comparisons between studies are compromised by differences in study design, diagnostic criteria, and patient selection. Recently, attention has been drawn to the importance of an early diagnosis based on the use of new, refined, and sensitive biomarkers. However, the pathophysiology behind AKI remains unsolved and ambiguous, which limits the usefulness of both traditional and new diagnostic tools. Furthermore, this gap in the understanding of AKI may be responsible for the lack of a specific preventive intervention or treatment.
Keywords: congenital heart disease; cardiac surgical procedures; acute kidney injury; children